2005
DOI: 10.4049/jimmunol.174.2.1118
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for CD28 May Not Be Absolute for Collagen-Induced Arthritis: Study with HLA-DQ8 Transgenic Mice

Abstract: CD28 is required to achieve optimal T cell activation to an Ag. To determine the role CD28 costimulation plays in collagen-induced arthritis, we have generated DQ8 transgenic, CD28-deficient mice. DQ8 mice deficient for CD28 had comparable numbers of CD4 and CD8 T cells as DQ8.CD28+/+ mice. DQ8.CD28−/− mice develop collagen-induced arthritis with delayed onset and less severity than DQ8.CD28+/+ mice. T cells from DQ8.CD28−/− mice did not respond to type II collagen efficiently in vitro, although the response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…These observations suggested a crucial role of Ii chain in cell selection and the proper functioning of HLA molecules in transgenic mice. In addition to the chaperone molecule such as Ii, costimulatory molecules like CD28 also function normally in transgenic mice as observed by studies using DQ8.CD28−/− mice [26]. These studies show that the HLA transgenes work with endogenous molecules suggesting the transgenic mice are functional and can provide good models to study various HLA-associated human diseases.…”
Section: Hla Transgenic Mice As Model For Rheumatoid Arthritismentioning
confidence: 85%
“…These observations suggested a crucial role of Ii chain in cell selection and the proper functioning of HLA molecules in transgenic mice. In addition to the chaperone molecule such as Ii, costimulatory molecules like CD28 also function normally in transgenic mice as observed by studies using DQ8.CD28−/− mice [26]. These studies show that the HLA transgenes work with endogenous molecules suggesting the transgenic mice are functional and can provide good models to study various HLA-associated human diseases.…”
Section: Hla Transgenic Mice As Model For Rheumatoid Arthritismentioning
confidence: 85%
“…CD4 + T cells from DQ8.CD28 −/− mice showed reduced in vitro responses but could be primed to antigen to mount primary and secondary responses. Using DQ8.CD28 −/− mice, we have shown that CD28 is not required for development of CIA, although in the absence of CD28 onset of disease was delayed (66). These studies suggested that for optimal response, CD28 is required, but in the absence of CD28, other costimulatory molecules can compensate for the function of CD28.…”
Section: Role Of Cd4+ and Cd8+ T Cells In Arthritismentioning
confidence: 99%
“…NKG2D is expressed by virtually all NK cells and activated CD8 + T cells, and subsets of γδ T cells and NKT cells 61, 62. In certain conditions, NKG2D is also expressed by CD4 + T cells, at least in humans6367.…”
Section: Receptors Mediating Immune Surveillancementioning
confidence: 99%